SAT0457 A Cross-Sectional Case-Control Study of Pulmonary Function in the Anti-Synthetase Syndrome. (9th June 2015) - Andersson, H.; Lund, M.B.; Sørhøy, H.G.; Garen, T.; Molberg, Ø.
Abstract : Background: Interstitial lung disease (ILD), myositis and anti-aminoacyl tRNA synthetase (aaRS) antibodies are the key disease components of the Antisynthetase syndrome (ASS). Several studies indicate that the ILD in ASS often causes restrictive ventilation impairment, but quantitative data on lung function and physical capacity are largely missing. Objectives: To assess pulmonary function tests (PFT) and six minutes walking distance (6MWD) in a cohort of ASS-patients and compare the results with healthy controls individually matched for sex and age. Methods: The Oslo University Hospital (OUH) ASS cohort is a single referral center cohort that includes 97 patients identified with positive aaRS antibodies, ILD and/or myositis in the period from 1994 to 2011. The current, cross-sectional study included 68 of the 71 ASS patients in the cohort that were alive by September 2011 (the last three patients refused participation). Sex and age-matched healthy controls were randomly collected from the National People Register of Norway in an 1:1 proportion (N=67). Thus, 68 patients and 67 controls were eligible to perform 6MWD and PFT. PFT included forced vital capacity (FVC), forced expiratory volume in one second (FEV1) and diffusing capacity of the lung for Carbon monoxide (DLCO). The study was performed during the period of Sept 2011-June 2014 and approved by the regional committee of health and medical research ethics in South-East Norway. Paired samples T-test was used for statistical significance (p<0.05). Results: The study cohort included 45 female and 23 male ASS patients (53 with anti-Jo-1 antibodies, 6 anti-PL-7 positive and 9 anti-PL-12 positive) with mean age 47 years at diagnosis. The PFT and 6MWD was performed median 71 months after diagnosis (6-362). Altogether, 66/68 ASS patients had a clinical ILD diagnosis, and 50/68 had myositis. Mean FVC in the ASS patients was 2.90 l compared to 3.73 l in the control group, a mean difference of 0.83 l (29%) (p<0.000). In the patients, the mean FEV1 was 2.29 l; 0.63 l (28%) lower than in the controls (p<0.000). Mean DLCO in the patients was 5.56 mmol/kPa.min, compared to 8.40 mmol/kPa.min in the controls, a mean difference of 2.84 mmol/kPa.min (51%) (p<0.000). The ASS patients had a mean 6MWD of 543 meters, the corresponding value in the controls was 659 m, giving a difference of 116 m (21%) (p<0.000). Conclusions: The data from this cross-sectional, case-controlled study demonstrates a highly significant difference in pulmonary function and 6MWD between ASS patients with median 71 months disease duration and matched healthy controls. The highest difference in PFT was seen in DLCO with 51% lower mean value in the ASS-group; possibly indicating that the ILD in ASS involves pulmonary vessel pathology. The study confirms the severity of pulmonary involvement in ASS and highlights the need for effective treatment strategies in this patient group. Disclosure of Interest: None declared